Health Care and Higher Education Governance:: The Role of the Economic Crisis - Vrangbæk, Karsten; Aarrevaara, Timo; Foss Hansen, Hanne; Keskimäki, Ilmo (Scandinavian Journal of Public Administration, 2017)
The paper contributes to the existing literature on reactions to economic shocks by adding a specific comparative focus on core welfare sectors within the Nordic region. Comparing crisis reactions across two countries using a framework of "cost saving", "reorganisation" and "programme" logic reveals patterns and constraints in different institutional settings. The paper concludes that Denmark and Norway initially tried to shelter the health care and higher education sectors, but they have moved on to more radical strategic responses as the crisis has persisted. Many similarities in the crisis reactions are apparent across the two countries and sectors, but important differences are also clear that may be ascribed to the specific institutional contexts.